1991
DOI: 10.1007/bf01809446
|View full text |Cite
|
Sign up to set email alerts
|

DNA-strand breaks limit survival in extreme dryness

Abstract: The inactivation of the anhydrobiotic organisms Bacillus subtilis (spores) and Deinococcus radiodurans during long-term exposure (up to several weeks) to extreme dryness (especially vacuum) is correlated with an increase in the number of DNA-strand breaks and other DNA lesions. Survival finally depends on the repair of DNA damages. Exposure of anhydrobiotic organisms to extreme dryness (e.g. on Mars or in space) for geological times will lead to so extended DNA lesions that recovery is extremely unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 17 publications
1
41
0
1
Order By: Relevance
“…Like, ionising radiation, the cytotoxicity of desiccation derives from the formation of DSBs (6,14,15). A substantial reduction in the molecular weight of D. radiodurans chromosomal DNA after exposure to a vacuum has been demonstrated (14).…”
Section: Nhej Pathway Protects M Smegmatis Against the Harmful Effecmentioning
confidence: 99%
See 1 more Smart Citation
“…Like, ionising radiation, the cytotoxicity of desiccation derives from the formation of DSBs (6,14,15). A substantial reduction in the molecular weight of D. radiodurans chromosomal DNA after exposure to a vacuum has been demonstrated (14).…”
Section: Nhej Pathway Protects M Smegmatis Against the Harmful Effecmentioning
confidence: 99%
“…A substantial reduction in the molecular weight of D. radiodurans chromosomal DNA after exposure to a vacuum has been demonstrated (14). Indeed, the extent of chromosomal fragmentation, adjudged to correspond to at least 60 DSBs, in D. radiodurans following desiccation is comparable to exposure to high doses of IR (6).…”
Section: Nhej Pathway Protects M Smegmatis Against the Harmful Effecmentioning
confidence: 99%
“…It is assumed that DNA double-strand breaks (DSB), which are the most critical damage caused by ionizing radiation (57) and desiccation (9,10,39) in vegetative cells, are also induced in bacterial spores. Spores of B. subtilis contain a single chromosome arranged in a toroidal shape (16,41); therefore, the homologous recombination pathway, which requires at least two homologous chromosomes, cannot operate on DSB during spore germination (55).…”
mentioning
confidence: 99%
“…When typical laboratory vacuum systems are used for simulated extreme desiccation, wild-type spores often exhibit no detectable killing (9,10). A major reason for spore resistance to these processes is protection of spore DNA by SASP.…”
mentioning
confidence: 99%
“…One of the most important issues to be dealt with is the removal of constituent water from DNA molecules during sample evacuation. It has been shown that the subtraction of such water initially leads to damage of the molecules in the form of single (SSB) and double strand breaks (DSB), and eventually complete decomposition of the DNA molecule to its basic building blocks, the nucleotides and nucleosides [78].…”
Section: Preparation Of Dna Films For Vacuum Studies Of Dna Damagementioning
confidence: 99%